2019
DOI: 10.1080/20002297.2019.1653124
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in the salivary microbiome of caries-active children

Abstract: Background and Objectives: Dental caries is a chronic disease affecting young children and has multi-factorial risk factors. The purpose of this work was to identify sex-specific differences in the salivary microbiota within caries-active children. Design: Saliva specimens were collected from 85 children (boys: 41; girls: 44) between the ages of 2-12 years. Salivary microbial DNA was subjected to PCR amplification using V3-V4 16S rDNA-specific primers and next-generation sequencing. Results: Significant sex di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Our finding on Selenomonas is discordant between sexes. Ortiz et al 25 showed that Selenomonas sps were associated with caries in girls, and a notably greater abundance of Selenomonas Genus probe 1 was observed with less frequent teeth brushing in adolescents with caries 20 , which is in line with our finding in girls. Taken together, we found that most of the caries-associated taxa were acid producers that cause demineralisation of tooth enamel.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding on Selenomonas is discordant between sexes. Ortiz et al 25 showed that Selenomonas sps were associated with caries in girls, and a notably greater abundance of Selenomonas Genus probe 1 was observed with less frequent teeth brushing in adolescents with caries 20 , which is in line with our finding in girls. Taken together, we found that most of the caries-associated taxa were acid producers that cause demineralisation of tooth enamel.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results are consistent with other studies that demonstrate that caries is more common in girls than in boys 34 , 35 . Ortiz et al 25 examined the sex-specific differences in the saliva microbiota in children with active caries and identified several species (including Rothia aeria, Neisseria flavescens , and Haemophilus pittmaniae ) that were higher in boys with active caries. Our findings are in line with these observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological differences among people can contribute to oral microbiota diversity and composition. Sex‐based differences have been reported in individuals that were stratified by disease status, 27 when large cohorts were examined, 28 in multple studies 29 . Age is also a critical factor, as oral microbiota change over time, 30,31 especially as older adults begin to wear dentures 32 .…”
Section: Factors That Influence the Oral Microbiota Composition Todaymentioning
confidence: 99%